The relative efficacy of price announcements and express communication for collusion: experimental findings - Harrington, Joseph E.; Hernan-Gonzalez, Roberto; Kujal, Praveen (Elsevier, 2016)
This study conducts experiments to determine the modes of communication that are able to produce and sustain collusion and how the efficacy of communication depends on market structure. Two communication treatments are considered: non-binding price announcements and unrestricted written communication. We find that price announcements are conducive to coordinating on a high price but only under duopoly and when firms are symmetric. The standard experimental finding that collusion without communication is rare when there are more than two firms is shown to be robust to allowing firms to make price announcements. When firms are asymmetric, price announcements do result in higher prices but there is little evidence that firms are coordinating their behavior. When firms are allowed to engage in unrestricted written communication, coordination on high prices occurs for all market structures. We find that the incremental value to express communication (compared to price announcements) is greater when firms are asymmetric and there are more firms.